Straight subjectivities in homonormative spaces: moving towards a new, 'dynamic' heteronormativity? - Bettani, Stefano (Gender, place and culture : a journal of feminist geography, 2015)
Although scholars have explored geographies of heterosexuality for a relatively long time, experiences of heterosexual subjects have been under-researched. Contributing to the discussions around how homo/straight spaces are negotiated, this study analyses how heterosexuals experience and define both homonormative and heteronormative spaces in Seattle. Through a series of interviews and focus groups with self-identified heterosexuals, I explore how these subjects interact with spaces that they recognize as being either straight or gay, and how they negotiate their own identities in relation to those spaces. I also describe how, while refusing to reject heterosexuality, the vast majority of participants expressed discomfort at being defined as someone with a fixed, stable sexual identity, and how they assumed gayness to be non-transgressive and fixed. The results show a paradoxical, complex picture, in which gayness is described as stable and normative, and heterosexuality is depicted as fluid and dynamic. The study illustrates an instance in which homo/straight binaries still shape people's imagination, while also offering an example of the messy interaction between homonormativity and heteronormativity. What is also suggested is that, experiencing homonormative spaces and performing 'dynamic' identities, the respondents renegotiate what being heterosexual means for them reinforcing, however, heterosexual dominance through the definition of a new 'dynamic' heteronormativity.